A randomized controlled trial of CBT-I and PAP for obstructive sleep apnea and comorbid insomnia: main outcomes from the MATRICS study. Issue 9 (14th March 2020) - Ong, Jason C; Crawford, Megan R; Dawson, Spencer C; Fogg, Louis F; Turner, Arlener D; Wyatt, James K; Crisostomo, Maria I; Chhangani, Bantu S; Kushida, Clete A; Edinger, Jack D; Abbott, Sabra M; Malkani, Roneil G; et al.
Abstract: Study Objectives: To investigate treatment models using cognitive behavioral therapy for insomnia (CBT-I) and positive airway pressure (PAP) for people with obstructive sleep apnea (OSA) and comorbid insomnia. Methods: 121 adults with OSA and comorbid insomnia were randomized to receive CBT-I followed by PAP, CBT-I concurrent with PAP, or PAP only. PAP was delivered following standard clinical procedures for in-lab titration and home setup and CBT-I was delivered in four individual sessions. The primary outcome measure was PAP adherence across the first 90 days, with regular PAP use (≥4 h on ≥70% of nights during a 30-day period) serving as the clinical endpoint. The secondary outcome measures were the Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI) with good sleeper (PSQI <5), remission (ISI <8), and response (ISI reduction from baseline >7) serving as the clinical endpoints. Results: No significant differences were found between the concomitant treatment arms and PAP only on PAP adherence measures, including the percentage of participants who met the clinical endpoint. Compared to PAP alone, the concomitant treatment arms reported a significantly greater reduction from baseline on the ISI ( p = .0009) and had a greater percentage of participants who were good sleepers ( p = .044) and remitters ( p = .008). No significant differences were found between the sequential and concurrent treatment models on any outcome measure. Conclusions: The findings from this study indicate that combining CBT-I with PAP is superior to PAP alone on insomnia outcomes but does not significantly improve adherence to PAP.